2005
DOI: 10.1007/s10903-005-3675-8
|View full text |Cite
|
Sign up to set email alerts
|

Refugees’ Perceptions of Healthy Behaviors

Abstract: This descriptive study explored refugees' knowledge and perceptions of nutrition, physical activity and smoking behaviors using the Health Promotion and Transtheoretical Models. A one-time interview used both closed- and open-ended questions. The sample included 31 adults from Bosnia, Iran, and Cuba. Refugees had some knowledge of a healthy diet and physical activity, and were aware of both benefits and barriers for health behaviors. They had a realistic perception of their weight (55% overweight), and none th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…In a study of Bosnian, Cuban, and Iranian refugees, 60% reported consumption of excessive energy, in general: 50%, too many sweets and 19%, too much fat (30). Cuban, Cambodian, and Hmong refugees indicated that an abundance of available food (18,23,30) and a variety of cuisines in the United States (23) compared with near-starvation and restricted food availability in regions of origin and/or refugee camps contributed to excess food consumption (23). Except for one intervention study (20,21), all were cross-sectional studies.…”
Section: Research Methods and Assessment Of Dietary Intakementioning
confidence: 99%
See 4 more Smart Citations
“…In a study of Bosnian, Cuban, and Iranian refugees, 60% reported consumption of excessive energy, in general: 50%, too many sweets and 19%, too much fat (30). Cuban, Cambodian, and Hmong refugees indicated that an abundance of available food (18,23,30) and a variety of cuisines in the United States (23) compared with near-starvation and restricted food availability in regions of origin and/or refugee camps contributed to excess food consumption (23). Except for one intervention study (20,21), all were cross-sectional studies.…”
Section: Research Methods and Assessment Of Dietary Intakementioning
confidence: 99%
“…In addition, one study showed that a supplementary program for B-12 deficiency resulted in increased refugee consumption of meat, eggs, and dairy products (20,21). Finally, a fairly common finding was that the consumption of sweets, sweetened beverages, fruit juices, and fast food increased in refugees after US resettlement (27,28,30,(31)(32)(33). The longer refugees lived in the United States, the more likely they were to consume added sugars, oils, seasonings, hot drinks, and vegetables (P < 0.05) (27).…”
Section: Research Methods and Assessment Of Dietary Intakementioning
confidence: 99%
See 3 more Smart Citations